PERAN INFLUENCER DALAM PEMASARAN DIGITAL: MENINGKATKAN LITERASI SISWA MELALUI WEBINAR INTERAKTIF - Cokki; Putri, Angely Olivia; Natalya, Yenny; Tiffany, Fransisca (Jurnal Serina Abdimas, 2024)
This PKM aims to increase the knowledge and insights of the younger generation, especially the students of SMAK Immanuel Pontianak, who are the PKM partners related to the role of influencers in the era of digital marketing. The limitations of literacy and learning related to digital marketing are challenges faced by the partners at present. Rapidly evolving digitization demands that students enhance their literacy and practical learning related to digital marketing. Therefore, the PKM team collaborates with the school to conduct interactive learning through webinars focusing on the role and benefits of using influencers in the digital marketing era. The webinar was attended by 70 students and consisted of several sessions covering material delivery, experimental activities, and question-and-answer sessions. The full contribution from both the school and the PKM team has facilitated the success of this webinar, enabling an increase in participants' literacy and deepening their insights into digital marketing. The PKM team also provides recommendations to partners in the form of steps that can be implemented to prepare students to face the challenges and opportunities in the continually evolving digital world. ABSTRAK PKM ini bertujuan untuk memperdalam pengetahuan dan wawasan generasi muda, khususnya siswa/i SMAK Immanuel Pontianak yang merupakan mitra PKM terkait peran influencer dalam era pemasaran digital. Keterbatasan literasi dan pembelajaran terkait pemasaran digital menjadi tantangan yang dihadapi mitra saat ini. Digitalisasi yang berkembang dengan pesat menuntut siswa/i untuk meningkatkan literasi dan pembelajaran yang aplikatif terkait pemasaran digital. Oleh karena itu, tim PKM bekerjasama dengan pihak sekolah untuk mengadakan pembelajaran interaktif melalui webinar yang berfokus pada peran dan manfaat penggunaan influencer di era pemasaran digital. Webinar diikuti oleh 70 siswa dan terdiri dari beberapa sesi yang meliputi penyampaian materi, kegiatan eksperimen, serta sesi tanya jawab. Kontribusi penuh dari pihak sekolah maupun tim PKM mendorong keberhasilan kegiatan webinar ini sehingga mampu meningkatkan literasi peserta dan memperdalam wawasan mereka tentang pemasaran digital. Tim PKM juga memberikan saran kepada mitra berupa langkah-langkah yang dapat diterapkan untuk mempersiapkan siswa/i dalam menghadapi tantangan dan peluang di dunia digital yang terus berkembang.